2008
DOI: 10.1071/ea08071
|View full text |Cite
|
Sign up to set email alerts
|

Host-plant resistance and biopesticides: ingredients for successful integrated pest management (IPM) in Australian sorghum production

Abstract: There are two major pests of sorghum in Australia, the sorghum midge, Stenodiplosis sorghicola (Coquillett), and the corn earworm, Helicoverpa armigera (Hübner). During the past 10 years the management of these pests has undergone a revolution, due principally to the development of sorghum hybrids with resistance to sorghum midge. Also contributing has been the adoption of a nucleopolyhedrovirus for the management of corn earworm. The practical application of these developments has led to a massive reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…armigera and H . punctigera in Australian cotton [53, 54] and show increasing parasitism with host density at the scale of fields [55]. Similarly, viral and fungal pathogens often show density-dependent spread through fields [56].…”
Section: Discussionmentioning
confidence: 99%
“…armigera and H . punctigera in Australian cotton [53, 54] and show increasing parasitism with host density at the scale of fields [55]. Similarly, viral and fungal pathogens often show density-dependent spread through fields [56].…”
Section: Discussionmentioning
confidence: 99%
“…The 213 lodging QTL identified as horizontal segments on each chromosome and colour-coded as follows: lodging QTL that significantly affect leaf senescence (green), lodging QTL that significantly affect plant height (pink), lodging QTL that significantly affect both leaf senescence and plant height (black), QTL did not affect either leaf senescence or plant height (red). Brown vertical bars to the right of each chromosome marked as "LDG" represent the locations of QTL previously detected for lodging (Kebede et al, 2001;Murray et al, 2008;Srinivasa Reddy et al, 2008); the black bars indicate the location of a QTL previously reported for charcoal rot and/or Fusarium stalk rot (Srinivasa Reddy et al, 2008;Adeyanju et al, 2015). The location of genes in the lignin biosynthesis pathways that co-located with lodging QTL detected in this study are highlighted in green to the right of each chromosome, and those that did not co-locate with lodging QTL are highlighted in blue (Bout & Vermerris, 2003;Saballos et al, 2009, 2012, Sattler et al, 2009, Walker et al, 2013, Jun et al, 2017Wang et al, 2017).…”
Section: Fields Of Research (For) Classificationmentioning
confidence: 99%
“…While heliothis oviposition may occur during vegetative growth with larvae feeding in the whorl, the pest causes the most damage to production immediately after flowering and over the following four weeks (Passlow et al, 1985) with developing larvae feeding initially on anthers and developing grains (Franzmann et al, 2008). Corn earworm Literature Review nucleopolyhedrovirus (NPV) is used almost exclusively in controlling corn earworm in sorghum, with the use of synthetic insecticides now on less than 5% of the treated crop area (Franzmann et al, 2008).…”
Section: Insect Pestsmentioning
confidence: 99%
“…Chemical pesticides have been used widely to control pests in agriculture for many years with premium efficiency. However, increasing resistance to existing chemical pesticides (Franzmann et al, 2008;Jacobson et al, 2009), increasing concern about the environment and food safety issues, and the desire of farmers to use safer pesticides are all reasons for the interest in biopesticides. The use of biological approaches as alternatives for pest control is the smart choice of modern agriculture towards sustainable agriculture and organic farming practices.…”
Section: Baculovirus Biopesticidesmentioning
confidence: 99%
“…are the major pests of field crops worldwide and it becomes difficult to control them because of the development of resistance to existing methods of chemical and biological control. In addition to the resistance to existing chemical pesticides, the increasing concern about the environment and food safety issues, and the desire of farmers to use safer pesticides are all reasons for the interest in biopesticides (Franzmann et al, 2008;Jacobson et al, 2009). Hence, the development of a viral biopesticide, as alternatives to the use of chemical pesticides, to control Helicoverpa pest species is potentially of great benefit for agriculture.…”
Section: Introductionmentioning
confidence: 99%